(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
In this article we have given an analytical guideline for complete toxicological analysis of postmortem materials in case of legal or clinical investigation. We have reviewed advantage and disadvantage of various routine methods and techniques used in crime laboratories for the extraction and identification of toxicants, we also emphasized on the utility of various modern instruments in post mortem toxicology. The purpose of this reviewed is provide a guide lines to analysts and encourage the use of modern analytical techniques in forensic toxicological practices. A brief description of result interpretation is also mentioned.